The Anthropocene: is there a geomorphological case?. Issue 4 (28th January 2013) - Brown, Antony G.; Tooth, Stephen; Chiverrell, Richard C.; Rose, James; Thomas, David S. G.; Wainwright, John; Bullard, Joanna E.; Thorndycraft, Varyl R.; Aalto, Rolf; Downs, Peter
ABSTRACT The 'Anthropocene', as used to describe the interval of recent Earth history during which humans have had an 'overwhelming' effect on the Earth system, is now being formally considered as a possible new geological Epoch. Such a new geological time interval (possibly equivalent to the Pleistocene Epoch) requires both theoretical justification as well as empirical evidence preserved within the geological record. Since the geological record is driven by geomorphological processes that produce terrestrial and near‐shore stratigraphy, geomorphology has to be an integral part of this consideration. For this reason, the British Society for Geomorphology (BSG) has inaugurated a Fixed Term Working Group to consider this issue and advise the Society on how geomorphologists can engage with debates over the Anthropocene. This ESEX Commentary sets out the initial case for the formalisation of the Anthropocene and a priori considerations in the hope that it will stimulate debate amongst, and involvement by, the geomorphological community in what is a crucial issue for the discipline. The Working Group is now considering the practical aspects of such a formalization including the relative magnitude problem, the boundary problem and the spatial diachrony of 'anthropogenic geomorphology'. Copyright © 2013 John Wiley & Sons, Ltd.